Evaluation of the use of Favipiravir on the Hematology value of COVID-19 patients at Anna Bekasi Hospital in 2021 - Feri Setiadi; Ardy Tanfil T; Widyastuti Widyastuti (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2023)
The COVID-19 pandemic caused by the SARS-CoV-2 virus occurred in Indonesia in early 2020. Favipiravir was used as an antiviral for the disease due to an emergency. The results of routine hematological examinations of inpatients can be used as a parameter to predict the patient's risk of severity and the effect of using favipiravir antiviral. This study aimed to determine the effect of using favipiravir on hematological values in COVID-19 patients. The method used in this research is cross-sectional. The data collection method was carried out retrospectively with the data source in the form of medical records at Anna Bekasi Selatan Hospital in 2021. The total sample that included the inclusion criteria in this study was 83 patients. The results of the study between before and after the use of favipiravir in patients without comorbidities were significant differences in the values of the Neutrophil Lymphocyte Ratio (p: 0.003), Lymphocytes (p: 0.000), Platelets (p: 0.009) while in the value of hematocrit (p: 0.185) ) and hemoglobin (p:0.069) did not experience a significant difference. Patients with comorbid comorbidities using favipiravir had significant differences in hematological values, namely hemoglobin (p: 0.007), hematocrit (p: 0.004), platelets (p: 0.000) while the value of the Neutrophil Lymphocyte Ratio (p: 0.260) and lymphocytes (p: 0.234) did not experience a significant difference. Favipiravir is known to have a positive correlation with hematological values, in patients with COVID-19 infection without comorbidities using favipiravir it is known that the Neutrophil Lymphocyte Ratio value has decreased while the Lymphocyte and Platelet values have increased. However, it is known that the hemoglobin and hematocrit values did not experience a significant difference before consuming favipiravir and after consuming favipiravir.